Improving Family Food Security through the Implementation of Budikdamber at Balai Sakinah Aisyiyah (BSA) Treko Village, Magelang Regency - Ika Afifah Nugraheni; Dinar Mindrati Fardhani (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
The COVID-19 pandemic that has occurred throughout the world, including Indonesia, has affected all areas of people's lives. Family food security is one of the areas affected due to restrictions on activities in the community. One of the efforts that can be made to parse and improve family food security is to implement mindfulness which is carried out independently. This can be a solution for BSA members of Treko Village, Magelang Regency who are affected by the COVID-19 pandemic because they are able to help meet family food availability. The purpose of this service activity is to provide education and training to BSA members so they are able to strengthen family food security during a pandemic. The method of implementation is carried out in a blended manner, including (1) licensing and consolidation, (2) education and demonstrations, and (3) monitoring and consulting services. Kale plants and catfish are the choices cultivated by BSA members of Treko Village through Budikdamber. Partners get online education through social media groups about the benefits of budikdamber. In addition, offline training is conducted to provide direct education regarding the preparation of buckets for cultivation, planting media and how to care for budikdamber. Based on the results of the business analysis, members of the BSA Desa Treko who apply the budikdamber can save Rp. 448,000 per year on family expenses. This can help the family economy during the COVID-19 pandemic.